Efficacy of Implementation of a Chest Pain Center at a Community Hospital. Issue 4 (December 2017) - Davis, Alexandra; Chiu, Jason; Lau, Stanley K.; Kok, Yih Jen; Wu, Jonathan Y. H.
Abstract : Introduction: Chest pain is the second leading cause for emergency department (ED) visits in the United States; however, <20% of the patients have acute coronary syndrome that require immediate attention. The HEART score is designed for rapid risk stratification of ED chest pain patients using the following criteria: history, electrocardiogram, age, risk factors, and troponin. It has been shown to be superior in identifying patients with low (HEART score 0–3) and high (7–10) risk of major adverse cardiac events, who can then be rapidly discharged or admitted for intervention. Objective: This retrospective review and assessment sought to evaluate the efficacy of implementation of a Chest Pain Center (CPC) at a predominantly Asian-based community hospital in the United States. Additionally, this assessment sought to evaluate the effectiveness and safety of a HEART protocol in the first 4 months after its adoption. Materials and Methods: The facility implemented the CPC, an observation unit, in October 2016. ED physicians risk stratified patients using the HEART score. The guidelines allow ED physicians to stratify patients into 3 categories: to discharge low-risk patients, observe moderate-risk patients in the CPC, and admit high-risk patients. Patients in the CPC received additional diagnostic work-up under the care of ED physicians and cardiologists for less than 24 hours. In addition, CPC patients were followed-up 2 and 30 days after discharge. Results: A total of 172 patients presented at the ED with a chief complaint of chest pain. The majority of the patients were classified into the moderate-risk group (n = 101). Low-risk patients spent significantly less hours in the hospital than the moderate- and high-risk groups, and the high-risk group spent more time in the hospital than the moderate-risk group. The staff followed-up with 74 CPC patients through telephone calls to assess if patients were still experiencing chest pain and if they had followed-up with a cardiologist or primary care physician. The 2- and 30-day survival rates were 100% and 97%, respectively. Discussion: The data showed a significant reduction in total length of stay for all chest pain patients. This retrospective program evaluation demonstrated some evidence in using HEART score to safely risk stratify chest pain patients to the appropriate level of care. As healthcare moves from a fee-for-service environment to value-based purchasing, hospitals need to devise and implement innovative strategies to provide efficient, beneficial, and safe care for the patients.